2017
DOI: 10.1038/srep40206
|View full text |Cite|
|
Sign up to set email alerts
|

The driving force of prophages and CRISPR-Cas system in the evolution of Cronobacter sakazakii

Abstract: Cronobacter sakazakii is an important foodborne pathogens causing rare but life-threatening diseases in neonates and infants. CRISPR-Cas system is a new prokaryotic defense system that provides adaptive immunity against phages, latter play an vital role on the evolution and pathogenicity of host bacteria. In this study, we found that genome sizes of C. sakazakii strains had a significant positive correlation with total genome sizes of prophages. Prophages contributed to 16.57% of the genetic diversity (pan gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…In this study, we further found that a "complete" cas gene cluster of subtype I-F and CRISPR6 (an additional CRISPR array besides the previous five) were integrated in the conserved region adjacent to CRISPR3 (25). The repeat sequence of CRISPR6 was the same as that of CRISPR3 (25). CRISPR3 and CRISPR6 combined with full cas genes formed the subtype I-F CRISPR-Cas system.…”
Section: Distribution Of Crispr-cas Subtypes Among 240mentioning
confidence: 60%
See 2 more Smart Citations
“…In this study, we further found that a "complete" cas gene cluster of subtype I-F and CRISPR6 (an additional CRISPR array besides the previous five) were integrated in the conserved region adjacent to CRISPR3 (25). The repeat sequence of CRISPR6 was the same as that of CRISPR3 (25). CRISPR3 and CRISPR6 combined with full cas genes formed the subtype I-F CRISPR-Cas system.…”
Section: Distribution Of Crispr-cas Subtypes Among 240mentioning
confidence: 60%
“…In our earlier study, we found five types of CRISPR arrays in the conserved site of C. sakazakii strains, but only CRISPR1 and CRISPR2 neighbored the cas genes of the subtype I-E CRISPR-Cas system (25). In this study, we further found that a "complete" cas gene cluster of subtype I-F and CRISPR6 (an additional CRISPR array besides the previous five) were integrated in the conserved region adjacent to CRISPR3 (25). The repeat sequence of CRISPR6 was the same as that of CRISPR3 (25).…”
Section: Distribution Of Crispr-cas Subtypes Among 240mentioning
confidence: 88%
See 1 more Smart Citation
“…Even CRISPR 462 arrays sharing a single set of cas genes may vary greatly in acquisition rate [57]. 463 Similarly, arrays with slightly different consensus repeat sequences may differ in length, 464 despite sharing a set of cas genes [58], which suggests a functional role for repeat 465 sequence modifications in determining spacer insertion rates. Despite this, we found no 466 clear link between array length and repeat sequence in our data, possibly due to a 467 weakly array-length dependent spacer loss rate.…”
mentioning
confidence: 99%
“…Even CRISPR arrays sharing a single set of cas genes may vary 445 greatly in acquisition rate [39], and our data suggests a link between consensus 446 repeat sequence and acquisition rate. Arrays with slightly different consensus 447 repeat sequences may differ in length, despite sharing a set of cas genes [52]. 448 This suggests a functional role for repeat sequence modifications in determining 449 spacer insertion rates.…”
mentioning
confidence: 99%